2011
DOI: 10.17796/jcpd.35.4.l43h3354705u2574
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of Intranasal Midazolam, Ketamine and their Combination for Sedation of Young Uncooperative Pediatric Dental Patients: A Triple Blind Randomized Crossover Trial

Abstract: Objective: The purpose of this study was to evaluate and compare the efficacy and safety of intranasal (IN)administration of midazolam (M), ketamine (K) and their combination (MK) to produce moderate sedation in young, uncooperative pediatric dental patients. Study design: In this three stage crossover trial forty five uncooperative ASA type-1 children, who required dental treatment, were randomly assigned to receive one of the three drugs/combination by IN route during three subsequent visits. The efficacy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 4 publications
2
55
2
Order By: Relevance
“…Seven studies (264 participants) were included (Fig 1 and S2 Text) [14,[21][22][23][24][25][26]. Excessive heterogeneity in outcome measures, study design, comparators, dosing, and indications for sedation precluded meta-analysis for any of the studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven studies (264 participants) were included (Fig 1 and S2 Text) [14,[21][22][23][24][25][26]. Excessive heterogeneity in outcome measures, study design, comparators, dosing, and indications for sedation precluded meta-analysis for any of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of included studies can be found in Table 1 and included children undergoing dental procedures (n = 5) [21,22,[24][25][26], laceration repair (n = 1) [14], and gastric aspiration (n = 1) [23]. No quasi-randomized trials were eligible.…”
Section: Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[9,10] However, this route may be unpredictable, and frustration often arises when children refuse to accept the sedative medication. [9,11] The oral route is the oldest and most economical of all routes of drug administration. It is also the most universally accepted method.…”
Section: Department Of Paedodontics Saveetha Dental College Chennaimentioning
confidence: 99%